2013
DOI: 10.1007/s00586-013-2763-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of intraspinal facet cysts following microsurgical bilateral decompression via a unilateral approach for treatment of degenerative lumbar disease

Abstract: Purpose Primary intraspinal facet cysts in the lumbar spine are uncommon, but it is unclear whether cyst incidence increases following decompression surgery and if these cysts negatively impact clinical outcome. We examined the prevalence, clinical characteristics, and the risk factors associated with intraspinal facet cysts after microsurgical bilateral decompression via a unilateral approach (MBDU). Methods We studied 230 patients treated using MBDU for lumbar degenerative disease (133 men and 97 women; mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…These techniques focus on the preservation of posterior elements such as the paraspinal muscles, supraspinatus and intraspinous ligaments, and intervertebral joints, for which favorable clinical outcomes have been reported in lumbar canal stenosis (LCS) patients. 2 , 6 , 7 , 8 , 10 , 11 , 14 , 15 Because impairment of scoliosis or instability after decompression can be minimized by posterior element preservation, MIS decompression indications have expanded to lumbar disease, including DLS or degenerative lumbar spondylolisthesis (DS). However, no consensus has yet been reached regarding these indications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques focus on the preservation of posterior elements such as the paraspinal muscles, supraspinatus and intraspinous ligaments, and intervertebral joints, for which favorable clinical outcomes have been reported in lumbar canal stenosis (LCS) patients. 2 , 6 , 7 , 8 , 10 , 11 , 14 , 15 Because impairment of scoliosis or instability after decompression can be minimized by posterior element preservation, MIS decompression indications have expanded to lumbar disease, including DLS or degenerative lumbar spondylolisthesis (DS). However, no consensus has yet been reached regarding these indications.…”
Section: Introductionmentioning
confidence: 99%
“…Microsurgical bilateral decompression via a unilateral approach (MBDU) has been performed for numerous degenerative lumbar diseases, including DLS or DS, at our institution. 10 , 14 The MIS decompression method was previously reported by McCulloch and Young for complete decompression on the contralateral side to treat degenerative lumbar spine disease ( Figure 1 ). 16 Although we achieved satisfactory results in several patients, we experienced some unfavorable postoperative outcomes that required revision postoperatively because of degenerative changes in the decompressed disc.…”
Section: Introductionmentioning
confidence: 99%
“…Conservative treatment consists of bed rest, analgesics plus anti-inflammatory drugs, physical therapy, bracing, transcutaneous electrical stimulation, epidural or intra-articular steroid injections [14].…”
Section: Surgical Treatmentsmentioning
confidence: 99%
“…four (4) patients required drainage of abundant wound secretions, one of which, when cultured, tested positive for s. aureus. 6 In a prospective analysis, Kato et al 11 identified facet joint synovial cysts in 38 (16.5%) out of 230 patients who had undergone ULBM during one year of follow-up. Twenty-four (24) of them had Figure 3.…”
Section: (Figures 1 2 3 and 4)mentioning
confidence: 99%
“…The preoperative risk factors for cyst formation were instability, anterior-posterior translation greater than 3 mm in flexion-extension (or 2.47, p=0.26), scoliotic disc with wedge >5° in Ap radiograph (or 2.23, p=0.048), and change in sagittal balance, and distance >50mm from the promontory to the C7 plumb line (or 2.22, p=0.045). 11 In a 5-year follow-up published in 2011, Toyoda h et al presented the following findings from a series of 57 patients (27 with LSS without instability, 20 with degenerative spondylolisthesis (dS), and 10 with degenerative lumbar scoliosis (dLS) with neurogenic claudication who underwent ULMB. The average JoA score was 13.8 ± 3.6 points prior to surgery, improving to 24.9 ± 3.1 points after three months and 22.6 ± 4.7 points at the end of follow-up.…”
Section: (Figures 1 2 3 and 4)mentioning
confidence: 99%